The strategic uses of race to legitimize 'social mix' urban redevelopment. (2nd January 2019) - Mele, Christopher
ABSTRACT: This article contends examines how racialization – the strategic employment of racial discourses to both define- and legitimize-specific social and spatial changes – serves as an adaptive and strategic means for city leaders and developers to control, define, plan and implement efforts to reshape impoverished neighborhoods. The deployment of racial tropes and narratives, such as diversity and 'social mix', organize and make legible redevelopment and its consequences of displacement for communities of poor minority residents. Urban development initiatives are imagined, worked out, legitimated and reconciled in an urban politics that relies on the deployment of racialized discourses of colorblindness, inclusivity and diversity. Drawing on a case study of redevelopment of Regent Park in Toronto, Canada, the paper examines how minorities are placed in the position of combatting socioeconomic and spatial inequalities, including displacement, on racial terms set by white elites.